2021
DOI: 10.1177/23197145211052817
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Experiential Quality on Behavioural Intention of Customers in Banking Services: The Moderating Role of Experiential Satisfaction

Abstract: This article investigates the relationship between experiential quality and behavioural intention of the consumers towards banking services during the pandemic situation. The study also examines the role of experiential satisfaction as a moderator between experiential quality and behavioural intentions. The data are collected through a self-administered structured questionnaire from 560 account holders of public sector banks in India. The data are analysed using PLS-SEM to find the empirical results of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Before the analysis of data, extreme values (i.e., outliers) have been identified with the help of Z‐score values for univariate cases (absolute value of Z being more than 3.29 indicates outlier) and by employing the Mahalanobis distance method for multivariate cases as recommended by Bag et al (2021). By applying the procedure, six and three respondents are detected in the two analyses and, therefore, not considered in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Before the analysis of data, extreme values (i.e., outliers) have been identified with the help of Z‐score values for univariate cases (absolute value of Z being more than 3.29 indicates outlier) and by employing the Mahalanobis distance method for multivariate cases as recommended by Bag et al (2021). By applying the procedure, six and three respondents are detected in the two analyses and, therefore, not considered in the final analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Satisfaction also acts as a driving force for technology adoption. Research work by Bag et al (2021) identifies the influence of experiential quality on behavioural intention of an individual towards banking services. The study also revealed that experiential satisfaction has moderating effect on experiential quality and behavioural intention among consumers.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, the experience received by the customer will also be different. The customer experience in traditional banking (Bag et al, 2021; and electronic banking (Cruz et al, 2010) has been investigated by several researchers; however, the dimension of digital banking 4.0 experience quality has not been much explored. For that reason, there is a need to further investigate the dimensions of digital banking 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the experience received by the customer will also be different. The customer experience in traditional banking (Bag et al. , 2021; Wu et al.…”
Section: Introductionmentioning
confidence: 99%